Changes in the prevalence of hepatitis B virus and its related factors in Inner Mongolia between 2006 and 2020 - Ding, Xuejie; Zhang, Zhongbing; Li, Cheng; Song, Hui; Ding, Shuna; Zhou, Yu; Ren, Xianyun; Hou, Fei; Wen, Xia; Li, Chunyan; Wang, Libo; Ma, Junqing; et al. (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to compare the prevalence of serum hepatitis B virus (HBV) markers in Inner Mongolia between 2006 and 2020.MethodsThe same sampling process was used in investigations conducted in 2006 and 2020. A multi-stage stratified random sampling method was used to select subjects aged 1–60 years old from 12 cities in Inner Mongolia. Blood samples were collected to detect serological HBV markers including hepatitis B surface antigen (HBsAg), hepatitis B surface antibody (HBsAb), and hepatitis B core antibody (HBcAb). The prevalence of serum biomarkers of hepatitis B, standardized by age and sex, was analyzed and compared between 2006 and 2020.ResultsThere were 6,304 subjects in 2006 and 6,500 in 2020. The prevalence of HBsAg was higher in 2006 than in 2020 (standardized 4.11% vs. 2.75%, p < 0.001). The results were observed for the serum biomarkers of HBsAb (standardized 41.40% vs. 42.14%, p = 0.39) between 2006 and 2020, as well as HBcAb (standardized 22.91% vs. 20.15%, p < 0.001). The hepatitis B vaccine (Hep B vaccine) provides protection against HBV infection. In 2006, the proportions of timely birth dose (TBD) and 3-dose Hep B vaccine coverage for individuals aged 1–14 years were 80.57 and 89.35%, respectively. By 2020, these proportions increased to 97.43 and 96.97%, respectively.ConclusionThe prevalence of HBsAg decreased significantly from 2006 to 2020 in Inner Mongolia, suggesting that the Hep B vaccine has made remarkable progress in safeguarding the population against hepatitis B infection.